Comprehensive insights into advances in ambient bioaerosols sampling, analysis and factors influencing bioaerosols composition - Bilal Sajjad (17017749) (2023)
While the study of bioaerosols has a long history, it has garnered heightened interest in the past few years, focusing on both culture-dependent and independent sampling and analysis approaches. Observations have been made regarding the seasonal fluctuations in microbial communities and their connection to particular ambient atmospheric factors. The study of airborne microbial communities is important in public health and atmospheric processes. Nevertheless, the establishment of standardized protocols for evaluating airborne microbial communities and utilizing microbial taxonomy as a means to identify distinct bioaerosols sources and seasonal patterns remains relatively unexplored. This article discusses the challenges and limitations of ambient bioaerosols sampling and analysis, including the lack of standardized methods and the heterogeneity of sources. Future prospects in the field of bioaerosols, including the use of high-throughput sequencing technologies, omics studies, spectroscopy and fluorescence-based monitoring to provide comprehensive incite on metabolic capacity, and activity are also presented. Furthermore, the review highlights the factors that affect bioaerosols composition, including seasonality, atmospheric conditions, and pollution levels. Overall, this review provides a valuable resource for researchers, policymakers, and stakeholders interested in understanding and managing bioaerosols in various environments. Other Information Published in: Environmental Pollution License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envpol.2023.122473